Strong interfacial coupling of MoS2/g-C3N4 van de Waals solids for highly active water reduction. (September 2016) - Fu, Wei; He, Haiyong; Zhang, Zhuhua; Wu, Chunyang; Wang, Xuewen; Wang, Hong; Zeng, Qingsheng; Sun, Linfeng; Wang, Xingli; Zhou, Jiadong; Fu, Qundong; Yu, Peng; et al.
Abstract: The facile and sustainable production of hydrogen through water reduction requires high performance catalyst consisting of earth abundant elements for the hydrogen evolution reaction (HER). Here we report the synthesis of ultrathin molybdenum disulfide/g-carbon nitride (MoS2 / g -C3 N4 ) vdW layers via an in situ interfacial engineering method. Such MoS2 / g -C3 N4 vdW layers show outstanding HER activity with comparable potential and Tafel slope to commercial Pt catalysts. Our experimental data and density functional theory (DFT) based calculations revealed that the unpreceded electrocatalytic performances originate from the strong interfacial coupling of vdW layers through out-of-plane Mo-N bonding, which therefore enhances hydrogen adsorption/reduction kinetics for HER. These findings will shed light on the programmable catalysts for low cost and highly active water reduction. Graphical abstract: Highlights: An in-situ interfacial engineering method is used to obtain vdW hybrids for HER. The strong interlayer coupling is present through out-of-plane Mo-N bonding. The excellent performance originates from this strong interlayer coupling. DFT shows the coupling enhances hydrogen adsorption/reduction kinetics for HER.